KYAI SEBAGAI PEMIMPIN DI PONDOK PESANTREN - Yazidul Busthomi (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
The requirements for kyai leadership at Islamic boarding schools are as follows: (1) Kyai at Islamic boarding schools have a good personality, and it is hoped that the kyai in leading his students at Islamic boarding schools can be honest, trustworthy, convey religious teachings, and be smart in leading students, (2) Kyai at Islamic boarding schools have knowledge and knowledge, that is, a leader must have sufficient ability, broad insight, and know the field he leads, (3) Kyai at Islamic boarding schools are able and willing with a sincere heart to do the tasks assigned to them. carried out, for example being able to educate, guide and teach his students at Islamic boarding schools well, diligently, patiently and sincerely in his heart, (4) Kyai at Islamic boarding schools have fair, honest and open characteristics, which means a leader must be able to accept ideas that come from its members. For example, receiving good suggestions from his subordinates, namely from the teachers at his Islamic boarding school, (5) Kyai at Islamic boarding schools must be able to foster cooperation and solidarity. A kyai as a leader is also expected to be able to grow his members to have commendable qualities such as honesty, keeping promises, trustworthiness, and courtesy. Meanwhile, the leadership role of the kyai in Islamic boarding schools includes: 1). As executor, 2) As person in charge, 3) As evaluator, 4) As mediator, 5) As protector. Keywords: Kyai, Leader, Islamic Boarding School